Glass panel, display screen and terminal
By plating a composite film layer with a specific structure on the surface of the glass panel substrate, the existing glass panels have insufficient scratch resistance, insufficient adhesion, and large differences in color difference, and glass panels with high Mohs hardness, strong adhesion and excellent optical performance are solved.
Patent Information
- Application Number
- CN202311163164.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-09-08
AI Technical Summary
The existing glass panels have limited scratch resistance, the outer coating protective film has insufficient adhesion, which makes it easy to fall off, and the color difference between before and after the coating is obvious, and the transmittance is significantly reduced.
The composite film layer with a specific structure is plated on the surface of the glass panel substrate, including a first base layer, a first barrier layer, a diamond-like film layer, a second barrier layer, a second base layer and a fingerprint-resistant layer. Through the synergistic effect of these layers, the Mohs hardness and adhesion of the glass panel are enhanced, and the color difference and transmittance difference before and after the coating are reduced.
It improves the scratch resistance of the glass panel, enhances the adhesion of the composite film layer, reduces the color difference and transmittance difference before and after coating, extends the service life of the composite film layer, and improves the comprehensive performance of the glass panel.
Smart Images

Figure CN119591327A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the technical field of glass panels, and in particular to a glass panel, a display screen, and a terminal. Background Art
[0002] At present, display screens using glass panels have been widely used in terminal devices such as mobile phones, tablet computers, and wearable products. In order to improve the scratch resistance of glass panels, the industry generally applies a protective film to the surface of the glass panel substrate, or directly coats the surface of the glass panel substrate with a protective film. However, the external protective film not only increases the cost of the device, but also reduces the optical properties of the screen, affecting the appearance of the product; the existing externally coated protective film has the following problems: limited ability to improve the scratch resistance of the glass panel, insufficient adhesion, easy detachment of the protective film, obvious color difference before and after coating, and obvious reduction in transmittance. Summary of the invention
[0003] In view of this, an embodiment of the present application provides a glass panel. By coating a composite film layer with a specific structure on the surface of the glass panel substrate, the glass panel can have a higher Mohs hardness to improve the scratch resistance of the glass panel, and the composite film layer has strong adhesion to the surface of the substrate and is not easy to fall off; the composite film layer can also reduce the color difference before and after coating to a certain extent and improve the transmittance.
[0004] In a first aspect, an embodiment of the present application provides a glass panel, comprising a glass panel substrate and a composite film layer disposed on a surface of the glass panel substrate, wherein the composite film layer comprises a first primer layer, a first barrier layer, a diamond-like film layer, a second barrier layer, a second primer layer and an anti-fingerprint layer which are sequentially stacked;
[0005] The materials of the first primer layer and the second primer layer are independently selected from one or more of silicon oxide and aluminum oxide, and the materials of the first barrier layer and the second barrier layer are independently selected from SiN x , CN x 、SiC x 、SiN x C y One or more of, wherein the values of x and y are in the range of 1-6; the thickness of the first coating layer is 2nm-30nm, the thickness of the first barrier layer is 1nm-20nm, the thickness of the diamond-like film layer is 3nm-40nm, the thickness of the second barrier layer is 1nm-20nm, the thickness of the second coating layer is 2nm-30nm, the thickness of the anti-fingerprint layer is less than or equal to 20nm, and the thickness of the composite film layer is less than 100nm.
[0006] The glass panel provided in the embodiment of the present application can have a higher Mohs hardness, reduce the color difference and transmittance difference before and after coating, and have strong adhesion of the composite film layer on the surface of the substrate by coating the composite film layer on the surface of the glass panel substrate. In the composite film layer, the first coating layer is contacted and stacked with the glass panel substrate, and the first coating layer can improve the adhesion of the composite film layer on the glass panel substrate, reduce the risk of the composite film layer falling off, and improve the reliability of the glass panel; the diamond-like film layer has high hardness, can improve the anti-scratch ability of the glass panel, and is conducive to reducing the total thickness of the composite film layer. In addition, the diamond-like film layer can also reduce the color difference before and after the composite film layer is coated; the first barrier layer and the second barrier layer are arranged to improve the overall hardness of the glass panel, and can prevent the adverse effects of oxidation of the diamond-like film layer during the preparation process of the composite film layer and the use of the glass panel, so that the glass panel can better maintain high hardness for a long time; the anti-fingerprint layer can reduce the residue of fingerprints, stains, etc. on the glass panel during use, and improve the user experience; the second coating layer can improve the adhesion of the anti-fingerprint layer, so that the glass panel maintains long-term anti-fouling performance. In addition, the present application controls the total thickness of the composite film layer to less than 100nm by reasonably regulating the thickness of each layer in the composite film layer to a smaller value. Under the synergistic effect of each film layer, it can better take into account the hardness, adhesion and optical properties, so that the stress of the composite film layer is controlled at a low level, and effectively avoids the problems of surface shape changes of the glass panel substrate and shedding of the composite film layer caused by the film layer stress, improves the adhesion of the composite film layer on the surface of the glass panel substrate, and extends the service life of the composite film layer, thereby obtaining a glass panel with excellent comprehensive performance to better meet the needs of terminal equipment.
[0007] In the embodiment of the present application, the composite film layer further includes a first optical film layer disposed between the first primer layer and the first barrier layer, and / or a second optical film layer disposed between the second primer layer and the second barrier layer; the first optical film layer and the second optical film layer are used to adjust the transmittance of the glass panel. The provision of the first optical film layer and / or the second optical film layer can effectively reduce the influence of the introduction of the composite film layer on the transmittance and hue of the glass panel, so that the glass panel can still have a high visible light transmittance after coating, so as to meet the application requirements of the display screen.
[0008] The present application sets the first optical film layer and the second optical film layer to adjust and improve the optical performance of the composite film layer by utilizing thin film interference. Thin film interference refers to the interference phenomenon caused by two beams of reflected light formed after a beam of light is reflected by two surfaces of a thin film.
[0009] In the embodiment of the present application, the thickness of the first optical film layer is 5nm-30nm; the thickness of the second optical film layer is 5nm-20nm. Suitable thicknesses of the first optical film layer and the second optical film layer can effectively improve the optical performance of the composite film layer, optimize the hue and optical transmittance of the glass panel, and ensure its reliable adhesion on the surface of the glass panel.
[0010] In the embodiment of the present application, the first optical film layer and the second optical film layer are a laminated structure formed by two or more sub-layers, and the material of each sub-layer is selected from silicon, aluminum, niobium, titanium or zirconium oxide, nitride, SiAl x O y N z Any one or more of the above, wherein the values of x, y, and z are in the range of 1 to 6. The optical film layer prepared by the above materials can effectively improve the visible light transmittance of the composite film layer, thereby better reducing the adverse effect of the composite film layer on the transmittance of the glass panel substrate.
[0011] In an embodiment of the present application, the first optical film layer includes at least one first sublayer and at least one second sublayer alternately stacked, and the first sublayer and the second sublayer have different refractive indices.
[0012] In an embodiment of the present application, the number of layers of the first sub-layer is 1-12 layers, and the number of layers of the second sub-layer is 1-12 layers.
[0013] In an embodiment of the present application, the second optical film layer includes at least one third sublayer and at least one fourth sublayer alternately stacked, and the third sublayer and the fourth sublayer have different refractive indices.
[0014] In the implementation manner of the present application, the number of layers of the third sub-layer is 1-12 layers, and the number of layers of the fourth sub-layer is 1-12 layers.
[0015] In the embodiment of the present application, the silicon oxide includes one or more of SiO2 and SiO; the aluminum oxide includes Al2O3. The first base layer and the second base layer are coated with silicon oxide and aluminum oxide, which can be closely combined with the surface of the glass panel substrate and improve the roughness of the surface of the glass panel substrate, thereby improving the adhesion of the subsequent film layer on the surface of the glass panel substrate.
[0016] In an embodiment of the present application, the niobium oxide includes one or more of NbO, NbO2, Nb2O3, and Nb2O5; the titanium oxide includes TiO2; the zirconium oxide includes ZrO2; the silicon nitride includes Si3N4; the aluminum nitride includes AlN; the niobium nitride includes one or two of NbN and Nb2N, the titanium nitride may be TiN, TiN2, Ti2N, Ti3N, Ti4N, Ti3N4, Ti3N5, and Ti5N6, and the zirconium nitride includes ZrN.
[0017] Diamond-like carbon film (DLC film for short) is an amorphous carbon film with a diamond-like structure. Its basic component is carbon, and it has high hardness, high resistivity, and good optical properties. Carbon elements can include diamond (Diamond) in which carbon atoms are bonded to each other in the form of sp3 bonds; and graphite (Graphite) in which carbon atoms are bonded to each other in the form of sp2 bonds. In diamond-like film, carbon atoms are bonded to each other in the form of sp3 and sp2 bonds. Diamond-like film is a metastable long-range disordered amorphous material. The bonding method between carbon atoms is covalent bonds, which mainly include sp2 and sp3 hybrid bonds. Diamond-like film has the excellent properties of both diamond and graphite.
[0018] In the embodiment of the present application, the diamond-like film layer includes a diamond-like film doped with any one or more doping elements selected from silicon, aluminum, titanium, zirconium, molybdenum, nitrogen and hydrogen. By doping the diamond-like film with the above elements, the hue effect caused by carbon hybridization can be effectively reduced, and the hue of the entire composite film layer can be optimized together with the first primer layer, the first barrier layer, the second barrier layer, the second primer layer, the first optical film layer and / or the second optical film layer, thereby improving the appearance of the glass panel and better improving the problem of poor visual experience caused by the color difference between the composite film layer and the non-detached part after the partial detachment.
[0019] In the embodiment of the present application, the atomic percentage of non-carbon elements in the diamond-like carbon thin film layer is less than 40%. Appropriate control of the content of non-carbon elements can improve the performance of the diamond-like carbon thin film layer due to doping while better maintaining the original good performance of the diamond-like carbon.
[0020] In the embodiment of the present application, the sp3 hybrid bonds in the diamond-like carbon film layer account for more than 30% of the total amount of sp2 hybrid bonds and sp3 hybrid bonds. Controlling the content of sp3 hybrid bonds in the diamond-like carbon film layer to a higher proportion is conducive to obtaining higher hardness.
[0021] In the embodiment of the present application, the atomic percentage of non-carbon elements in the diamond-like carbon film layer and the proportion of sp3 hybrid bonds can be measured by XPS (X-ray photoelectron spectroscopy).
[0022] In the embodiment of the present application, the Mohs hardness of the glass panel 100 is greater than or equal to 7. A Mineralab Mohs hardness pen is used to scratch the coated surface of the glass panel 100 at 45° with a load of 750g. If there is no visible scratch to the naked eye, it is considered that the glass panel 100 has passed the corresponding Mohs hardness test of the Mohs hardness pen. The glass panel has a higher Mohs hardness and can better resist scratches, thereby improving the anti-scratch ability of the glass panel and improving the user experience.
[0023] In the embodiment of the present application, the number of times that the composite film layer 20 resists rubber friction without falling off on the glass panel substrate 10 is greater than 10,000 times. This value is obtained by rubbing back and forth on the coated surface of the glass panel using a minoan eraser, a weight of 1000g, and a speed of 40 turns / min. The high number of times that the composite film layer resists rubber friction without falling off indicates that the composite film layer has strong adhesion on the glass panel substrate, which can extend the service life of the composite film layer and improve the long-term service reliability of the glass panel.
[0024] In the implementation manner of the present application, the color difference value △E between the glass panel and the glass panel substrate is less than 1.5. That is to say, the color difference of the glass panel substrate before and after the composite film layer is coated is very small. The color difference value △E is a parameter generated as an auxiliary indicator of the Lab value. It is usually a color difference expressed in the form of a numerical value, that is, the degree of difference between two colors. The smaller the value of △E, the closer the two colors are; conversely, the larger the value of △E, the more obvious the difference between the colors. Therefore, △E can quantitatively measure the color difference between two colors. △E can be calculated by the following formula:
[0025]
[0026] Among them, △L, △a, and △b represent the differences between the two colors in brightness, a* axis, and b* axis respectively. In other words, these three factors jointly determine the degree of difference between the colors. Therefore, the value of △E is actually generated by the combined effect of these three factors.
[0027] In the embodiment of the present application, the average transmittance of the glass panel in the wavelength range of 450nm-940nm is greater than or equal to 85%. The glass panel of the embodiment of the present application has a high optical transmittance, which can improve the display effect of the display screen using the glass panel and improve the user experience.
[0028] In the implementation manner of the present application, the 550nm transmittance reduction value of the glass panel relative to the glass panel substrate is less than 0.5%, or the 550nm transmittance of the glass panel is greater than or equal to the 550nm transmittance of the glass panel substrate. The glass panel of the present application is provided with a composite film layer of a special structure on the surface of the glass panel substrate, and the composite film layer has little effect on the optical transmittance of the glass panel, and can even be consistent with or higher than the transmittance of the glass panel substrate.
[0029] A second aspect of an embodiment of the present application provides a method for preparing a glass panel, comprising:
[0030] A composite film layer is plated on the surface of the glass panel substrate, wherein the composite film layer includes a first primer layer, a first barrier layer, a diamond-like film layer, a second barrier layer, a second primer layer and an anti-fingerprint layer which are stacked in sequence;
[0031] The first primer layer, the first barrier layer, the diamond-like carbon film layer, the second barrier layer and the second primer layer are prepared by magnetron sputtering, and the anti-fingerprint layer is prepared by evaporation; the materials of the first primer layer and the second primer layer are independently selected from one or more of silicon oxide and aluminum oxide, and the materials of the first barrier layer and the second barrier layer are independently selected from SiN x , CN x 、SiC x 、SiN x C y One or more of, wherein the values of x and y are in the range of 1-6; the thickness of the first coating layer is 2nm-30nm, the thickness of the first barrier layer is 1nm-20nm, the thickness of the diamond-like film layer is 3nm-40nm, the thickness of the second barrier layer is 1nm-20nm, the thickness of the second coating layer is 2nm-30nm, the thickness of the anti-fingerprint layer is less than or equal to 20nm, and the thickness of the composite film layer is less than 100nm.
[0032] In the implementation manner of the present application, the composite film layer further includes:
[0033] The first optical film layer is disposed between the first primer layer and the first barrier layer, and / or the second optical film layer is disposed between the second primer layer and the second barrier layer; the first optical film layer and the second optical film layer are prepared by magnetron sputtering. The method for preparing the glass panel provided in the embodiment of the present application has a simple process and is easy to control, and can realize large-scale production.
[0034] The third aspect of the embodiment of the present application provides a display screen, including a display screen module and a glass panel covering the display screen module, wherein the glass panel includes the glass panel described in the first aspect of the embodiment of the present application. The display screen using the glass panel of the embodiment of the present application can better protect the display screen module and has a better display effect.
[0035] The embodiment of the present application also provides a terminal, including a housing, and a circuit board located inside the housing, the housing including a display screen, the display screen including a glass panel and a display screen module arranged inside the glass panel, the glass panel including the glass panel described in the first aspect of the embodiment of the present application. The terminal using the glass panel of the embodiment of the present application has a good display effect. The terminal can be a terminal device such as a mobile phone, a tablet computer, a laptop computer, a wearable product (a watch, a bracelet, glasses), a vehicle-mounted device, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 A schematic diagram of a cross-sectional structure of a glass panel 100 provided in an embodiment of the present application;
[0037] Figure 2 A schematic cross-sectional structure diagram of a glass panel 100 provided in another embodiment of the present application;
[0038] Figure 3 A schematic diagram of a cross-sectional structure of a glass panel 100 provided in yet another embodiment of the present application;
[0039] Figure 4 A schematic diagram of a cross-sectional structure of a glass panel 100 provided in yet another embodiment of the present application;
[0040] Figure 5 is a schematic diagram of the cross-sectional structure of the first optical film layer 27 of the embodiment of the present application;
[0041] Figure 6 is a schematic diagram of the cross-sectional structure of the second optical film layer 28 of the embodiment of the present application;
[0042] Figure 7 A schematic diagram of a cross-sectional structure of a display screen 200 provided in an embodiment of the present application;
[0043] Figure 8 A schematic diagram of a cross-sectional structure of a terminal 300 provided in an embodiment of the present application;
[0044] Fig. 9 The transmittance curve of the glass panel prepared in Example 1 of the present application;
[0045] Fig.10 The transmittance curve of the glass panel prepared in Example 2 of the present application;
[0046] Fig.11 This is the transmittance curve of the glass panel prepared in Example 3 of the present application. DETAILED DESCRIPTION
[0047] The embodiments of the present application will be described below in conjunction with the drawings in the embodiments of the present application.
[0048] At present, mobile phones, tablet computers, wearable products and other terminal devices all use glass panels to cover the display screen components. In order to improve the scratch resistance of the glass panel, a method commonly used in the industry is to coat a protective film on the surface of the glass panel substrate. However, the existing externally coated protective films have the following problems: limited improvement in the scratch resistance of the glass panel, insufficient adhesion, easy fall-off of the protective film, obvious color difference before and after coating, and obvious reduction in transmittance. In order to solve the above problems to a certain extent, an embodiment of the present application provides a glass panel, which can make the glass panel have a higher Mohs hardness to improve the scratch resistance of the glass panel by coating a composite film layer with a specific structure on the surface of the glass panel substrate, and the composite film layer has strong adhesion to the substrate surface and is not easy to fall off; the composite film layer can also reduce the color difference before and after coating and improve the transmittance to a certain extent.
[0049] See also Figure 1 , Figure 1 Schematic diagram of the cross-sectional structure of a glass panel provided in an embodiment of the present application. The glass panel 100 provided in an embodiment of the present application comprises a glass panel substrate 10 and a composite film layer 20 disposed on the surface of the glass panel substrate 10. The composite film layer 20 comprises a first primer layer 21, a first barrier layer 22, a diamond-like film layer 23, a second barrier layer 24, a second primer layer 25 and an anti-fingerprint layer 26 which are sequentially stacked from the surface of the glass panel substrate 10 outward.
[0050] The materials of the first bottom layer 21 and the second bottom layer 25 are independently selected from one or more of silicon oxide and aluminum oxide, and the materials of the first barrier layer 22 and the second barrier layer 24 are independently selected from SiN x , CN x 、SiC x 、SiN x C y One or more of, wherein the values of x and y are in the range of 1-6; the thickness of the first coating layer 21 is 2nm-30nm, the thickness of the first barrier layer 22 is 1nm-20nm, the thickness of the diamond-like film layer 23 is 3nm-40nm, the thickness of the second barrier layer 24 is 1nm-20nm, the thickness of the second coating layer 25 is 2nm-30nm, the thickness of the anti-fingerprint layer 26 is less than or equal to 20nm, and the thickness of the composite film layer 20 is less than 100nm.
[0051] The glass panel provided in the embodiment of the present application can have a higher Mohs hardness, reduce the color difference and transmittance difference before and after coating, and have strong adhesion of the composite film layer on the surface of the substrate by coating the composite film layer on the surface of the glass panel substrate. In the composite film layer, the first primer layer is in contact with the glass panel substrate and laminated, and the first primer layer can improve the adhesion of the composite film layer on the glass panel substrate, reduce the risk of the composite film layer falling off, and improve the reliability of the glass panel; the diamond-like film layer has high hardness, can improve the anti-scratch ability of the glass panel, and is conducive to reducing the total setting thickness of the composite film layer. In addition, the diamond-like film layer can also reduce the color difference before and after the composite film layer is coated; the setting of the first barrier layer and the second barrier layer is conducive to the improvement of the overall hardness of the glass panel, and can prevent the adverse effects of oxidation of the diamond-like film layer during the preparation process of the composite film layer and the use of the glass panel, so that the glass panel can better maintain high hardness for a long time; the setting of the anti-fingerprint layer can reduce the residue of fingerprints, stains, etc. on the glass panel during use, and improve the user experience; the setting of the second primer layer can improve the adhesion of the anti-fingerprint layer, so that the glass panel maintains long-term anti-fouling performance. In addition, the present application controls the total thickness of the composite film layer to less than 100nm by reasonably regulating the thickness of each layer in the composite film layer to a smaller value. Under the synergistic effect of each film layer, it can better take into account the hardness, adhesion and optical properties, so that the stress of the composite film layer is controlled at a low level, and effectively avoids the problems of surface shape changes of the glass panel substrate and shedding of the composite film layer caused by the film layer stress, improves the adhesion of the composite film layer on the surface of the glass panel substrate, and extends the service life of the composite film layer, thereby obtaining a glass panel with excellent comprehensive performance to better meet the needs of terminal equipment.
[0052] In the embodiment of the present application, the first coating layer 21 includes one or more of silicon oxide and aluminum oxide. Silicon oxide may be, for example, silicon dioxide (SiO2), silicon monoxide (SiO), etc. Aluminum oxide may be, for example, aluminum oxide (Al2O3). The first coating layer 21 is in contact with the glass panel substrate 10. The first coating layer 21 is coated with silicon oxide and aluminum oxide to be tightly combined with the surface of the glass panel substrate 10, and the roughness of the surface of the glass panel substrate 10 may be improved, thereby improving the adhesion of the subsequent film layer on the surface of the glass panel substrate 10.
[0053] In the implementation manner of the present application, the thickness of the first bottom layer 21 can be 2nm-30nm. In some embodiments, the thickness of the first bottom layer 21 can be, for example, 2nm, 3nm, 5nm, 6nm, 8nm, 10nm, 12nm, 14nm, 15nm, 17nm, 18nm, 20nm, 22nm, 25nm, 28nm, 30nm. The first bottom layer is set to a suitable thickness and connected between the glass panel substrate and the first barrier layer, which can ensure that the film layer structure provided on the first bottom layer forms a strong bond with the glass panel substrate, and can also keep the total thickness of the composite film layer at a relatively small level.
[0054] In the embodiment of the present application, the material of the first barrier layer 22 is selected from SiN x , CN x 、SiC x 、SiN x C y One or more of, wherein the values of x and y are in the range of 1-6. Specifically, the values of x and y can be selected from 1, 2, 3, 4, 5, and 6, respectively. The first barrier layer 22 adopts the above materials to obtain a higher hardness, and can better protect the diamond-like film layer from being oxidized or doped with other impurities that affect the performance during the preparation and use process, which is also conducive to the diamond-like film layer to achieve a low thickness setting.
[0055] In the embodiment of the present application, the thickness of the first barrier layer 22 is 1nm-20nm. In some embodiments, the thickness of the first barrier layer 22 can be, for example, 1nm, 2nm, 3nm, 5nm, 6nm, 8nm, 10nm, 12nm, 14nm, 15nm, 17nm, 18nm, 20nm. A smaller first barrier layer thickness can improve the overall adhesion of the composite film layer and improve the overall performance of the glass panel.
[0056] In some embodiments of the present application, the first primer layer and the first barrier layer have different refractive indices, the first primer layer is silicon oxide, and the first barrier layer is SiN x , CN x 、SiC x or SiN x C y In some embodiments of the present application, the first base layer is aluminum oxide, and the first barrier layer is SiN x , CN x 、SiC x or SiN x C y .
[0057] Diamond-like carbon film (DLC film for short) is an amorphous carbon film with a diamond-like structure. Its basic component is carbon, and it has high hardness, high resistivity, and good optical properties. Carbon elements can include diamond (Diamond) in which carbon atoms are bonded to each other in the form of sp3 bonds; and graphite (Graphite) in which carbon atoms are bonded to each other in the form of sp2 bonds. In diamond-like film, carbon atoms are bonded to each other in the form of sp3 and sp2 bonds. Diamond-like film is a metastable long-range disordered amorphous material. The bonding method between carbon atoms is covalent bonds, which mainly include sp2 and sp3 hybrid bonds. Diamond-like film has the excellent properties of both diamond and graphite.
[0058] In the embodiment of the present application, the diamond-like film layer 23 includes a diamond-like film doped with any one or more elements of silicon, aluminum, titanium, zirconium, molybdenum, nitrogen and hydrogen. By doping the diamond-like film with the above elements, it is beneficial to improve the hardness of the diamond-like film layer and / or reduce the hue effect caused by carbon hybridization, optimize the hue of the entire composite film layer, improve the appearance and display effect of the glass panel, and better avoid the problem of poor visual experience caused by the color difference between the composite film layer and the non-shedding part after the partial detachment. In some embodiments, the diamond-like film layer 23 includes a doping element, for example, the diamond-like film layer 23 is a nitrogen-doped diamond film layer, a silicon-doped diamond film layer, an aluminum-doped diamond film layer, a titanium-doped diamond film layer, a zirconium-doped diamond film layer, or a molybdenum-doped diamond film layer. In some embodiments, the diamond-like film layer 23 includes two or more doping elements, for example, the diamond-like film layer 23 is a nitrogen-silicon co-doped diamond film layer, a nitrogen-aluminum co-doped diamond film layer, etc.
[0059] In the embodiment of the present application, the atomic percentage of non-carbon elements in the diamond-like film layer is less than 40%. In some embodiments, the atomic percentage of non-carbon elements in the diamond-like film layer is 1%-40%, for example, 1%, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 39%. Non-carbon elements include the above-mentioned doping elements. Suitable control of the content of non-carbon elements can make the diamond-like film layer obtain performance improvement due to doping while better maintaining the original good performance of diamond-like.
[0060] In the embodiment of the present application, the sp3 hybrid bonds in the diamond-like film layer account for more than 30% of the total amount of sp2 hybrid bonds and sp3 hybrid bonds. In some embodiments, the proportion of sp3 hybrid bonds is more than 40%, more than 45%, more than 50%, more than 60% or more than 70%. Controlling the content of sp3 hybrid bonds in the diamond-like film layer to a higher proportion is conducive to obtaining higher hardness.
[0061] In the embodiment of the present application, the thickness of the diamond-like film layer 23 is 3nm-40nm. In some embodiments, the thickness of the diamond-like film layer 23 is 3nm, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm. Controlling the thickness of the diamond-like film layer within this range can improve the hardness of the glass panel, thereby improving the scratch resistance, and can also keep the total thickness of the composite film layer at a small value, thereby improving its adhesion to the surface of the glass panel substrate.
[0062] See also Figure 2 , Figure 3 and Figure 4 , Figure 2 A schematic cross-sectional structure diagram of a glass panel 100 provided in another embodiment of the present application; Figure 3 A schematic diagram of a cross-sectional structure of a glass panel 100 provided in yet another embodiment of the present application; Figure 4 A schematic diagram of the cross-sectional structure of a glass panel 100 provided in another embodiment of the present application. In the embodiment of the present application, the composite film layer 20 further includes a first optical film layer 27 disposed between the first coating layer 21 and the first barrier layer 22, and / or a second optical film layer 28 disposed between the second coating layer 25 and the second barrier layer 24; the first optical film layer 27 and the second optical film layer 28 are used to adjust the transmittance of the glass panel. The provision of the first optical film layer and / or the second optical film layer can effectively reduce the influence of the introduction of the composite film layer on the transmittance and hue of the glass panel, so that the glass panel can still have a high visible light transmittance after coating to meet the application requirements of the display screen.
[0063] The present application sets the first optical film layer and the second optical film layer to adjust and improve the optical performance of the composite film layer by utilizing thin film interference. Thin film interference refers to the interference phenomenon caused by two beams of reflected light formed after a beam of light is reflected by two surfaces of a thin film.
[0064] In some embodiments of the present application, Figure 2 As shown, the composite film layer 20 includes a first optical film layer 27 disposed between the first primer layer 21 and the first barrier layer 22, but does not include a second optical film layer 28. In some embodiments of the present application, as Figure 3 As shown, the composite film layer 20 includes a second optical film layer 28 disposed between the second primer layer 25 and the second barrier layer 24, but does not include the first optical film layer 27. Figure 4 As shown, the composite film layer 20 includes a first optical film layer 27 disposed between the first primer layer 21 and the first barrier layer 22 , and a second optical film layer 28 disposed between the second primer layer 25 and the second barrier layer 24 .
[0065] The first optical film layer 27 and the second optical film layer 28 are provided in the present application to adjust and improve the optical performance of the composite film layer 20 by utilizing thin film interference. Thin film interference refers to the interference phenomenon caused by two beams of reflected light formed after a beam of light is reflected by two surfaces of a thin film.
[0066] In the embodiment of the present application, the first optical film layer 27 and the second optical film layer 28 are both laminated structures formed by two or more sub-layers, and the material of each sub-layer is independently selected from oxides, nitrides, SiAl2O3, SiAl2O3, Al2O3, NiO2, NiO3, NiO4, or NiO3. x O y N z Any one or more of, wherein the values of x, y, and z are in the range of 1-6. The first optical film layer 27 and the second optical film layer 28 may be materials including two or more materials with different refractive indices to constitute two or more sublayers with different refractive indices. Among them, silicon oxide may be, for example, silicon dioxide (SiO2), silicon monoxide (SiO), etc. Aluminum oxide may be, for example, aluminum oxide (Al2O3). Niobium oxide may be niobium monoxide, niobium dioxide, niobium trioxide, niobium pentoxide, or a mixture of two or more thereof, titanium oxide may be titanium dioxide, and zirconium oxide may be zirconium dioxide. Silicon nitride may be silicon nitride Si3N4, aluminum nitride may be aluminum nitride AlN, niobium nitride may be NbN, Nb2N, titanium nitride may be TiN, TiN2, Ti2N, Ti3N, Ti4N, Ti3N4, Ti3N5, Ti5N6, and zirconium nitride may be ZrN. SiAl x O y N z The values of x, y, and z can be selected from 1, 2, 3, 4, 5, and 6 respectively. The optical film layer prepared by the above materials can effectively improve the visible light transmittance of the composite film layer, thereby better reducing the adverse effect of the composite film layer on the transmittance of the glass panel substrate.
[0067] See also Figure 5 , Figure 5The cross-sectional structure diagram of the first optical film layer 27 of the embodiment of the present application is shown in FIG. The first optical film layer 27 includes at least one first sublayer 271 and at least one second sublayer 272 alternately stacked, and the refractive index of the first sublayer 271 is different from the refractive index of the second sublayer 272. For example, the refractive index of the first sublayer 271 may be less than the refractive index of the second sublayer 272, and the first optical film layer 27 may be in contact with the first primer layer 21, or the second sublayer 272; the first optical film layer 27 may be in contact with the first barrier layer 22, or the first sublayer 271, or the second sublayer 272. In the present application, in the first optical film layer 27, the number of layers of the first sublayer 271 may be 1-12, and the number of layers of the second sublayer 272 may be 1-12. Specifically, 1-12 layers may be, for example, 1 layer, 2 layers, 3 layers, 4 layers, 5 layers, 6 layers, 7 layers, 8 layers, 9 layers, 10 layers, 11 layers, or 12 layers. The number of layers of the first sublayer 271 and the second sublayer 272 may be the same or different. It is understandable that the material of the first sublayer 271 and the second sublayer 272 may be selected from oxides, nitrides, SiAl2O3, SiAl2O3, Al2O3, NiO2, NiO3, NiO4, or NiO3. x O y N z In some embodiments, the first sublayer 271 is silicon nitride Si3N4, and the second sublayer 272 is silicon dioxide SiO2. In some embodiments, the first sublayer 271 is silicon nitride Si3N4, and the second sublayer 272 is aluminum oxide Al2O3.
[0068] See also Figure 6 , Figure 6 The cross-sectional structure diagram of the second optical film layer 28 of the embodiment of the present application is shown in FIG. The second optical film layer 28 includes at least one third sublayer 281 and at least one fourth sublayer 282, which are alternately stacked. The refractive index of the third sublayer 281 is different from the refractive index of the fourth sublayer 282. For example, the refractive index of the third sublayer 281 may be less than the refractive index of the fourth sublayer 282. The second optical film layer 28 may be in contact with the second primer layer 25 through the third sublayer 281 or the second sublayer 272; the second optical film layer 28 may be in contact with the second barrier layer 24 through the third sublayer 281 or the fourth sublayer 282. In the present application, in the second optical film layer 28, the number of layers of the third sublayer 281 may be 1-12, and the number of layers of the fourth sublayer 282 may be 1-12. The number of layers 1 to 12 may be, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12. The number of layers of the third sublayer 281 and the fourth sublayer 282 may be the same or different. It is understood that the material of the third sublayer 281 and the fourth sublayer 282 may be selected from oxides, nitrides, SiAl2O3 ... x Oy N z In some embodiments, the third sublayer 281 is silicon nitride Si3N4, and the fourth sublayer 282 is silicon dioxide SiO2. In some embodiments, the third sublayer 281 is silicon nitride Si3N4, and the fourth sublayer 282 is aluminum oxide Al2O3.
[0069] In the present application, when the composite film layer 20 includes both the first optical film layer 27 and the second optical film layer 28, the first optical film layer 27 and the second optical film layer 28 may have the same composition structure or different composition structures. The number of sub-layers included in the first optical film layer 27 and the second optical film layer 28 may be the same or different. The thicknesses of the first optical film layer 27 and the second optical film layer 28 may be the same or different.
[0070] In the implementation manner of the present application, the thickness of the first optical film layer 27 is 5nm-30nm. In some embodiments, the thickness of the first optical film layer 27 is 5nm, 6nm, 8nm, 10nm, 12nm, 15nm, 18nm, 20nm, 22nm, 25nm, 30nm. The appropriate thickness of the first optical film layer can effectively improve the optical properties of the composite film layer, optimize the hue and optical transmittance of the glass panel, and ensure its reliable adhesion on the surface of the glass panel.
[0071] In the implementation manner of the present application, the thickness of the second optical film layer 28 is 5nm-20nm. In some embodiments, the thickness of the second optical film layer 28 is 5nm, 6nm, 8nm, 10nm, 12nm, 15nm, 18nm, 20nm. The appropriate thickness of the second optical film layer can effectively improve the optical properties of the composite film layer, optimize the hue and optical transmittance of the glass panel, and ensure its reliable adhesion on the surface of the glass panel.
[0072] In the embodiment of the present application, the second coating layer 25 includes one or more of silicon oxide and aluminum oxide. Silicon oxide can be, for example, silicon dioxide (SiO2), silicon monoxide (SiO), etc. Aluminum oxide can be, for example, aluminum oxide (Al2O3). The second coating layer 25 is in contact with the anti-fingerprint layer 26. The second coating layer 25 is coated with silicon oxide and aluminum oxide to enable the anti-fingerprint layer 26 to be tightly bonded to the glass panel substrate.
[0073] In the embodiment of the present application, the thickness of the second bottom layer 25 can be 2nm-30nm. In some embodiments, the thickness of the second bottom layer 25 can be, for example, 2nm, 3nm, 5nm, 6nm, 8nm, 10nm, 12nm, 14nm, 15nm, 17nm, 18nm, 20nm, 22nm, 25nm, 28nm, 30nm. The second bottom layer is set to a suitable thickness to ensure that the anti-fingerprint layer is strongly bonded to the glass panel substrate, and to keep the total thickness of the composite film layer at a relatively small level.
[0074] In the embodiment of the present application, the material of the second barrier layer 24 is selected from SiN x , CN x 、SiC x 、SiN x C y One or more of, wherein the values of x and y are in the range of 1-6. Specifically, the values of x and y can be selected from 1, 2, 3, 4, 5, and 6, respectively. The second barrier layer 24 adopts the above materials to obtain a higher hardness, and can better protect the diamond-like film layer from being oxidized or doped with other impurities that affect the performance during use, which is also conducive to the diamond-like film layer to achieve a low thickness setting.
[0075] In the embodiment of the present application, the thickness of the second barrier layer 24 is 1nm-20nm. In some embodiments, the thickness of the second barrier layer 24 can be, for example, 1nm, 2nm, 3nm, 5nm, 6nm, 8nm, 10nm, 12nm, 14nm, 15nm, 17nm, 18nm, 20nm. A smaller thickness of the second barrier layer can improve the overall adhesion of the composite film layer and improve the overall performance of the glass panel.
[0076] In some embodiments of the present application, the second primer layer and the second barrier layer have different refractive indices, the second primer layer is silicon oxide, and the second barrier layer is SiN x , CN x 、SiC x or SiN x C y In some embodiments of the present application, the second primer layer is aluminum oxide, and the second barrier layer is SiN x , CN x 、SiC x or SiN x C y .
[0077] In the composite film layer 20 of the present application, the materials and thicknesses of the first primer layer 21 and the second primer layer 25 may be the same or different. The materials and thicknesses of the first barrier layer 22 and the second barrier layer 24 may be the same or different.
[0078] In the embodiment of the present application, the material of the anti-fingerprint layer 26 is not limited as long as it can achieve the anti-fingerprint effect, for example, it can be a fluorine-containing material, and the fluorine-containing material can be, for example, perfluoropolyether.
[0079] In the embodiment of the present application, the thickness of the anti-fingerprint layer 26 is less than or equal to 20nm. In some embodiments, the thickness of the anti-fingerprint layer 26 is 3nm-20nm. In some embodiments, the thickness of the anti-fingerprint layer 26 is 3nm, 5nm, 6nm, 8nm, 10nm, 12nm, 15nm, 18nm, 20nm. Controlling the thickness of the anti-fingerprint layer to a smaller value can better control the total thickness of the composite film layer to a smaller value, thereby improving its adhesion to the surface of the glass panel substrate.
[0080] In the implementation mode of the present application, the thickness of the composite film layer 20 is less than 100nm. In some embodiments, the thickness of the composite film layer 20 is 10nm, 20nm, 30nm, 40nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm. Controlling the total thickness of the composite film layer below 100nm can control the stress of the composite film layer at a low level, effectively avoiding the problem of the surface shape change of the glass panel substrate and the shedding of the composite film layer caused by the film layer stress, improving the adhesion of the composite film layer on the surface of the glass panel substrate, and extending the service life of the composite film layer; in addition, the color difference of the appearance of the glass panel before and after coating can be minimized, thereby improving the user experience.
[0081] In the embodiment of the present application, the glass panel substrate 10 can be glass-ceramics or ordinary glass. In order to improve the mechanical properties of the glass panel, chemically strengthened glass-ceramics or chemically strengthened ordinary glass can be used. The thickness and performance parameters of the glass panel substrate 10 can be selected according to actual needs.
[0082] In the embodiment of the present application, the Mohs hardness of the glass panel 100 is greater than or equal to 7. A Mineralab Mohs hardness pen is used to scratch the coated surface of the glass panel 100 at 45° with a load of 750g. If there is no visible scratch to the naked eye, it is considered that the glass panel 100 has passed the corresponding Mohs hardness test of the Mohs hardness pen. The glass panel has a higher Mohs hardness and can better resist scratches, thereby improving the anti-scratch ability of the glass panel and improving the user experience.
[0083] In the embodiment of the present application, the number of times that the composite film layer 20 resists rubber friction without falling off on the glass panel substrate 10 is greater than 10,000 times. This value is obtained by rubbing back and forth on the coated surface of the glass panel using a minoan eraser, a weight of 1000g, and a speed of 40 turns / min. The high number of times that the composite film layer resists rubber friction without falling off indicates that the composite film layer has strong adhesion on the glass panel substrate, which can extend the service life of the composite film layer and improve the long-term service reliability of the glass panel.
[0084] In the embodiment of the present application, the color difference value △E between the glass panel 100 and the glass panel substrate 10 is less than 1.5. In some embodiments, the color difference value △E between the glass panel 100 and the glass panel substrate 10 is less than 1.0. In the embodiment of the present application, the color difference value △E between the glass panel 100 and the glass panel substrate 10 is less than 0.5. In other words, the color difference of the glass panel substrate before and after the composite film layer is coated is very small. The color difference value △E is a parameter generated as an auxiliary indicator of the Lab value. It is usually expressed as a color difference in the form of a numerical value, that is, the degree of difference between two colors. The smaller the value of △E, the closer the two colors are; conversely, the larger the value of △E, the more obvious the difference between the colors. Therefore, △E can quantitatively measure the color difference between two colors. △E can be calculated by the following formula:
[0085]
[0086] Among them, △L, △a, and △b represent the differences between the two colors in brightness, a* axis, and b* axis respectively. In other words, these three factors jointly determine the degree of difference between the colors. Therefore, the value of △E is actually generated by the combined effect of these three factors.
[0087] In the implementation manner of the present application, the average transmittance of the glass panel 100 in the wavelength range of 450nm-940nm is greater than or equal to 85%. In some embodiments, the average transmittance of the glass panel 100 in the wavelength range of 450nm-940nm is greater than or equal to 88%. In some embodiments, the average transmittance of the glass panel 100 in the wavelength range of 450nm-940nm is greater than or equal to 90%. The glass panel in the embodiment of the present application has a high optical transmittance, which can improve the display effect of the display screen using the glass panel and improve the user experience.
[0088] In the implementation manner of the present application, the 550nm transmittance reduction value of the glass panel 100 relative to the glass panel substrate 10 is less than 0.5%. The 550nm transmittance reduction value of the glass panel 100 relative to the glass panel substrate 10 is less than 0.3%. In some implementation manners of the present application, the 550nm transmittance of the glass panel is greater than or equal to the 550nm transmittance of the glass panel substrate. The glass panel of the present application is provided with a composite film layer of a special structure on the surface of the glass panel substrate. The composite film layer has little effect on the optical transmittance of the glass panel, and can even be consistent with or higher than the transmittance of the glass panel substrate, so that the glass panel still has a high transmittance after being coated with the composite film layer.
[0089] The glass panel of the embodiment of the present application has a high Mohs hardness, small color difference before and after coating, small transmittance difference, and strong adhesion of the composite film layer on the surface of the substrate. The glass panel can be used for terminal device display screens to improve product competitiveness.
[0090] The present application also provides a method for preparing the glass panel, including:
[0091] A composite film layer is plated on the surface of the glass panel substrate, wherein the composite film layer includes a first primer layer, a first barrier layer, a diamond-like film layer, a second barrier layer, a second primer layer and an anti-fingerprint layer which are stacked in sequence;
[0092] The first primer layer, the first barrier layer, the diamond-like carbon film layer, the second barrier layer and the second primer layer are prepared by magnetron sputtering, and the anti-fingerprint layer is prepared by evaporation.
[0093] In an embodiment of the present application, the composite film layer also includes a first optical film layer arranged between the first base layer and the first barrier layer, and / or a second optical film layer arranged between the second base layer and the second barrier layer; the first optical film layer and the second optical film layer are prepared by magnetron sputtering.
[0094] In one embodiment of the present application, a method for preparing a glass panel may include:
[0095] The cleaned glass panel substrate is placed in a sputtering coating machine, and a first primer layer is firstly coated on the surface of the glass panel substrate, and then a first barrier layer is coated on the first primer layer, and then a nitrogen-doped diamond-like film layer is coated on the first barrier layer, and then a second barrier layer is coated on the nitrogen-doped diamond-like film layer, and a second primer layer is coated on the second barrier layer, and finally an AF anti-fingerprint layer is evaporated on the second primer layer to obtain a glass panel.
[0096] The method for preparing the glass panel provided in the embodiment of the present application has a simple process and is easy to control, and can realize large-scale production.
[0097] See also Figure 7 , Figure 7The cross-sectional structure diagram of the display screen 200 provided in the embodiment of the present application comprises a display screen module 201 and a glass panel 100 covering the display screen module. The glass panel body 10 of the glass panel 100 is in direct contact with the display screen module 201. The glass panel 100 is used to provide protection for the display screen module 201 and can also be touched by the user. The display screen using the glass panel of the embodiment of the present application can better protect the display screen module and has a better display effect.
[0098] See also Figure 8 , Figure 8 The terminal 300 provided in the embodiment of the present application is a schematic diagram of a cross-sectional structure. The terminal 300 provided in the embodiment of the present application includes a housing 301 and a circuit board ( Figure 8 The housing 301 includes a display screen 200, and the display screen 200 includes a glass panel 100 and a display screen module 201 disposed inside the glass panel 100. The terminal using the glass panel of the embodiment of the present application has a good display effect. The terminal can be a mobile phone, a tablet computer, a laptop computer, a wearable product (a watch, a bracelet, glasses), a vehicle-mounted device, and other terminal devices.
[0099] The embodiments of the present application are further described below with reference to a plurality of embodiments.
[0100] Among them, transmittance and color difference are tested using optical testing equipment such as CM3600a. The hardness test uses a Mineralab Mohs hardness pen, loads 750g force, and scratches the coated surface of the glass panel at 45°. If there is no visible scratch to the naked eye, the glass panel is considered to have passed the corresponding Mohs hardness test of the Mohs hardness pen. The friction resistance test uses a Minoan eraser, loads a 1000g weight, and rubs back and forth on the coated surface of the glass panel at a speed of 40 turns / min. One back and forth rubbing is counted as one friction.
[0101] Example 1
[0102] The cleaned glass panel substrate is placed in a sputtering coating machine. A SiO2 primer layer with a thickness of 6 nm is firstly coated on the surface of the glass panel substrate. Then, a first optical film layer and a first barrier layer with a stacked structure of Si3N4 / SiO2 / Si3N4 / SiO2 / Si3N4 are coated on the primer layer. The total thickness of the first optical film layer and the first barrier layer is 30 nm. Then, a nitrogen-doped diamond-like film layer with a thickness of 20 nm is coated on the first optical film layer. Then, a nitrogen-doped diamond-like film layer with a thickness of 20 nm is coated on the nitrogen-doped diamond-like film layer. The stacking structure is a second optical film layer, a second barrier layer and a second primer layer of Si3N4 / SiO2 / Si3N4 / SiO2, with a total thickness of 20nm. Finally, an AF anti-fingerprint layer with a thickness of 8nm is evaporated on the second optical film layer to obtain a glass panel, whose stacking structure is glass / SiO2 / Si3N4 / SiO2 / Si3N4 / SiO2 / Si3N4 / nitrogen-doped diamond-like film layer / Si3N4 / SiO2 / Si3N4 / SiO2 / AF.
[0103] The performance test is as follows:
[0104] 1. Transmittance:
[0105] wavelength 450nm 550nm 650nm 750nm 850nm 940nm Transmittance after coating 91.4% 91.6% 91.8% 91.9% 92.2% 92.3% Transmittance before coating 89.9% 90.8% 91.2% 91.5% 92% 92.1%
[0106] Fig. 9 This is the transmittance curve of the glass panel prepared in Example 1.
[0107] 2. Hardness test:
[0108] Mohs hardness 6 passes, Mohs hardness 7 passes, and Mohs hardness 8 fails.
[0109] 3. Friction resistance test:
[0110] Resistant to rubber friction for more than 10,000 times.
[0111] 4. Color difference test:
[0112] Test results: The color difference before and after coating is less than 0.5.
[0113] Example 2
[0114] The cleaned glass panel substrate is placed in a sputtering coating machine. A SiO2 primer layer with a thickness of 15 nm is firstly coated on the surface of the glass panel substrate. Then, a first optical film layer and a first barrier layer with a stacked structure of Si3N4 / Al2O3 / Si3N4 / Al2O3 / Si3N4 are coated on the primer layer. The total thickness of the first optical film layer and the first barrier layer is 20 nm. Then, a nitrogen-doped diamond-like film layer with a thickness of 20 nm is coated on the first optical film layer. Then, a stacked structure of Si3N4 / Al2O3 / Si3N4 / Al2O3 / Si3N4 is coated on the nitrogen-doped diamond-like film layer. The second optical film layer, the second barrier layer and the second primer layer of the structure are Si3N4 / Al2O3 / Si3N4 / Al2O3, with a total thickness of 15nm. Finally, a 10nm thick AF anti-fingerprint layer is evaporated on the second optical film layer to obtain a glass panel, whose stacking structure is glass / SiO2 / Si3N4 / Al2O3 / Si3N4 / Al2O3 / Si3N4 / nitrogen-doped diamond-like film layer / Si3N4 / Al2O3 / Si3N4 / Al2O3 / AF.
[0115] The performance test is as follows:
[0116] 1. Transmittance test:
[0117] wavelength 450nm 550nm 650nm 750nm 850nm 940nm Transmittance after coating 88.2% 90.8% 91.6% 92.0% 92.5% 92.6%
[0118] Fig.10 This is the transmittance curve of the glass panel prepared in Example 2.
[0119] 2. Hardness test:
[0120] Mohs hardness 6 passes, Mohs hardness 7 passes, and Mohs hardness 8 fails.
[0121] 3. Friction resistance test:
[0122] Resistant to rubber friction for more than 10,000 times.
[0123] 4. Color difference test:
[0124] Test results: The color difference before and after coating is less than 0.5.
[0125] Example 3
[0126] The cleaned glass panel substrate is placed in a sputtering coating machine, and a first SiO2 primer layer with a thickness of 10 nm is first plated on the surface of the glass panel substrate. Then, a SiC first barrier layer is plated on the first primer layer, and the thickness of the first barrier layer is 20 nm. Subsequently, a nitrogen-doped diamond-like film layer with a thickness of 10 nm is plated on the first barrier layer, and then a second barrier layer and a second primer layer with a stacked structure of SiC / SiO2 are plated on the nitrogen-doped diamond-like film layer, and the total thickness of the two is 10 nm. Finally, a 15 nm thick AF anti-fingerprint layer is evaporated on the second primer layer to obtain a glass panel with a stacked structure of glass / SiO2 / SiC / nitrogen-doped diamond-like film layer / SiC / SiO2 / AF.
[0127] The performance test is as follows:
[0128] 1. Transmittance test:
[0129] wavelength 450nm 550nm 650nm 750nm 850nm 940nm Transmittance after coating 86.8% 88.7% 89.9% 90.7% 91.4% 92.1%
[0130] Fig.11 This is the transmittance curve of the glass panel prepared in Example 3.
[0131] 2. Hardness test:
[0132] Mohs hardness 6 passes, Mohs hardness 7 passes, and Mohs hardness 8 fails.
[0133] 3. Friction resistance test:
[0134] Resistant to rubber friction for more than 10,000 times.
[0135] 4. Color difference test:
[0136] Test results: The color difference before and after coating is less than 0.5.
[0137] From the above results, it can be seen that the glass panel of the embodiment of the present application has a composite film layer with a specific structure having a thickness of less than 100 nm on the surface of the glass panel substrate, so that the transmittance of the glass panel changes little before and after coating, and still has a high transmittance after coating the composite film layer, indicating that the composite film layer of the embodiment of the present application has little effect on the transmittance of the glass panel; the composite film layer has a high Mohs hardness and can improve the scratch resistance of the glass panel; the composite film layer has strong adhesion to the glass panel substrate, and the composite film layer does not fall off when rubbed with an rubber for more than 10,000 times, so that the composite film layer can be firmly combined with the surface of the glass panel substrate during service, and play a long-term protective role on the substrate.
[0138] It should be understood that the first, second and various numerical numbers involved in this document are only distinguished for the convenience of description and are not used to limit the scope of the present application.
[0139] In this application, "and / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone, where A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0140] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0141] In this application, “-” represents a range value, including the endpoint values at both ends. For example, the value of a can be 0.5-15, which means that the value of a can be between 0.5 and 15, and includes the endpoint values 0.5 and 15.
[0142] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
Claims
1. A glass panel, characterized in that: It comprises a glass panel substrate and a composite film layer arranged on the surface of the glass panel substrate, wherein the composite film layer comprises a first primer layer, a first barrier layer, a diamond-like film layer, a second barrier layer, a second primer layer and an anti-fingerprint layer which are sequentially stacked; The materials of the first primer layer and the second primer layer are independently selected from one or more of silicon oxide and aluminum oxide, and the materials of the first barrier layer and the second barrier layer are independently selected from SiN x , CN x 、SiC x 、SiN x C y One or more of, wherein the values of x and y are in the range of 1-6; the thickness of the first coating layer is 2nm-30nm, the thickness of the first barrier layer is 1nm-20nm, the thickness of the diamond-like film layer is 3nm-40nm, the thickness of the second barrier layer is 1nm-20nm, the thickness of the second coating layer is 2nm-30nm, the thickness of the anti-fingerprint layer is less than or equal to 20nm, and the thickness of the composite film layer is less than 100nm.
2. The glass panel according to claim 1, wherein: The composite film layer also includes a first optical film layer arranged between the first primer layer and the first barrier layer, and / or a second optical film layer arranged between the second primer layer and the second barrier layer; the first optical film layer and the second optical film layer are used to adjust the transmittance of the glass panel.
3. The glass panel according to claim 2, wherein: The thickness of the first optical film layer is 5nm-30nm; the thickness of the second optical film layer is 5nm-20nm.
4. The glass panel according to claim 2 or 3, characterized in that: The first optical film layer and the second optical film layer are a laminated structure formed by two or more sub-layers, and the material of each sub-layer is selected from oxides, nitrides, SiAl2O3, SiAl2O3, and SiAl2O3 of silicon, aluminum, niobium, titanium or zirconium. x O y N z Any one or more of the following, where the values of x, y, and z are in the range of 1-6.
5. The glass panel according to claim 4, wherein: The first optical film layer includes at least one first sublayer and at least one second sublayer alternately stacked, and the first sublayer and the second sublayer have different refractive indices.
6. The glass panel according to claim 5, wherein: The number of layers of the first sub-layer is 1-12, and the number of layers of the second sub-layer is 1-12.
7. The glass panel according to claim 4, wherein: The second optical film layer includes at least one third sublayer and at least one fourth sublayer alternately stacked, and the third sublayer and the fourth sublayer have different refractive indices.
8. The glass panel according to claim 7, wherein: The number of layers of the third sub-layer is 1-12, and the number of layers of the fourth sub-layer is 1-12.
9. The glass panel according to any one of claims 1 to 8, characterized in that: The silicon oxide includes one or more of SiO2 and SiO; the aluminum oxide includes Al2O3.
10. The glass panel according to any one of claims 4 to 8, characterized in that: The niobium oxide includes one or more of NbO, NbO2, Nb2O3, and Nb2O5; the titanium oxide includes TiO2; the zirconium oxide includes ZrO2; the silicon nitride includes Si3N4; the aluminum nitride includes AlN; the niobium nitride includes one or two of NbN and Nb2N, the titanium nitride may be TiN, TiN2, Ti2N, Ti3N, Ti4N, Ti3N4, Ti3N5, and Ti5N6, and the zirconium nitride includes ZrN.
11. The glass panel according to any one of claims 1 to 10, characterized in that: The diamond-like film layer includes a diamond-like film doped with any one or more doping elements of silicon, aluminum, titanium, zirconium, molybdenum, nitrogen and hydrogen.
12. The glass panel according to any one of claims 1 to 11, characterized in that: The atomic percentage of non-carbon elements in the diamond-like carbon film layer is less than 40%.
13. The glass panel according to any one of claims 1 to 12, characterized in that: The sp3 hybrid bonds in the diamond-like carbon film layer account for more than 30% of the total amount of sp2 hybrid bonds and sp3 hybrid bonds.
14. The glass panel according to any one of claims 1 to 13, characterized in that: The Mohs hardness of the glass panel is greater than or equal to 7.
15. The glass panel according to any one of claims 1 to 14, characterized in that: The composite film layer can withstand rubber friction on the glass panel substrate for more than 10,000 times without falling off.
16. The glass panel according to any one of claims 1 to 15, characterized in that: The color difference ΔE between the glass panel and the glass panel substrate is less than 1.
5.
17. The glass panel according to any one of claims 1 to 16, characterized in that: The average transmittance of the glass panel within the wavelength range of 450nm-940nm is greater than or equal to 85%.
18. The glass panel according to any one of claims 1 to 17, characterized in that: The 550nm transmittance reduction value of the glass panel relative to the glass panel substrate is less than 0.5%, or the 550nm transmittance of the glass panel is greater than or equal to the 550nm transmittance of the glass panel substrate.
19. A method for preparing a glass panel, characterized in that: include: A composite film layer is plated on the surface of the glass panel substrate, wherein the composite film layer includes a first primer layer, a first barrier layer, a diamond-like film layer, a second barrier layer, a second primer layer and an anti-fingerprint layer which are stacked in sequence; The first primer layer, the first barrier layer, the diamond-like carbon film layer, the second barrier layer and the second primer layer are prepared by magnetron sputtering, and the anti-fingerprint layer is prepared by evaporation; the materials of the first primer layer and the second primer layer are independently selected from one or more of silicon oxide and aluminum oxide, and the materials of the first barrier layer and the second barrier layer are independently selected from SiN x , CN x 、SiC x 、SiN x C y One or more of, wherein the values of x and y are in the range of 1-6; the thickness of the first coating layer is 2nm-30nm, the thickness of the first barrier layer is 1nm-20nm, the thickness of the diamond-like film layer is 3nm-40nm, the thickness of the second barrier layer is 1nm-20nm, the thickness of the second coating layer is 2nm-30nm, the thickness of the anti-fingerprint layer is less than or equal to 20nm, and the thickness of the composite film layer is less than 100nm.
20. The preparation method according to claim 19, characterized in that: The composite film layer also includes: A first optical film layer is disposed between the first primer layer and the first barrier layer, and / or a second optical film layer is disposed between the second primer layer and the second barrier layer; the first optical film layer and the second optical film layer are prepared by magnetron sputtering.
21. A display screen, characterized in that: It comprises a display screen module and a glass panel covering the display screen module, wherein the glass panel comprises the glass panel according to any one of claims 1 to 18.
22. A terminal, characterized in that: It comprises a shell and a circuit board located inside the shell, the shell comprises a display screen, the display screen comprises a glass panel and a display screen module arranged inside the glass panel, and the glass panel comprises the glass panel according to any one of claims 1-18.
Citation Information
Patent Citations
Coating for glass with improved scratch / wear resistance and oleophobic properties
CN107000382A
A high-hardness wear-resistant glass cover plate and a preparing method thereof
CN107746186A
Nano-structure DLC film, hardened glass, preparation device and preparation method of hardened glass
CN111153599A
Composite substrate structure and touch panel with same
CN204270267U
High-transparency protective glass, touch screen and touch screen displayer
CN204463071U
Cited By
Glass panel, display screen and terminal
EP4692012A1
Glass panel, display screen and terminal
WO2025051188A1